Protein Arginine Methyltransferase 5 Functions via Interacting Proteins - Liang, Zhenzhen; Wen, Chaowei; Jiang, Heya; Ma, Shumei; Liu, Xiaodong (Frontiers in Cell and Developmental Biology, 2021)
The protein arginine methyltransferases (PRMTs) are involved in such biological processes as transcription regulation, DNA repair, RNA splicing, and signal transduction, et al. In this study, we mainly focused on PRMT5, a member of type II PRMTs, functions mainly together with interacting proteins. It has been shown to be overexpressed in a wide variety of cancers and other diseases, and is involved in the regulation of hepatitis and hepatocellular carcinoma, cell cycle and apoptosis, spliceosome and various signaling pathways. In this study we analyzed the regulatory roles of PRMT5 and interacting proteins in various biological processes, mentioned-above, to elucidates for the first time the interaction between PRMT5 and its interacting proteins, the systemic analysis will fulfill the biological theory and contribute to the development of novel therapies.